Pemanfaatan Limbah Palet untuk Perabot Rumah Tangga Masyarakat Lokal Dusun Sarsang - Anton Topan; Alahudin, Muchlis (BADAN PENERBIT STIEPARI PRESS, 2025)
Pallet Wood is waste wood. The type of pallet wood has a medium to low hardness level, some types of wood include; sengon wood, camphor wood, randu wood and others. Pallet wood waste is used as household furniture including; tables, chairs, cupboards and other furniture. OMK (Catholic Young People) is an organization of Catholic youth; OMK activities, taking part in Sunday and religious day worship, guiding Sunday school, decorating the Church (Easter, Christmas and others), cleaning the church environment, and representing the church. In addition to religious activities there are also activities outside, including; sports, farming and others. The purpose of the service is counseling and training in making furniture for OMK in Sarsang Hamlet, Tanah Miring District. The method used in this service is counseling and training. The community involved in this service activity is the OMK Group and members of the St. Yoseph Church council. The results of this service activity are the OMK Group and members of the St. Yoseph Church council have the skills to process pallet wood waste as household furniture materials that have a sales value. In the furniture training, 2 tables, 2 long chairs and 2 small chairs were made. With the skills gained, it is hoped that residents can utilize wood waste, especially pallet wood, into functional furniture and of course have a selling value.